Textiles from Zawaydah, Naqada, Upper Egypt - Gleba, Margarita; Boudin, Mathieu; Di Pietro, Grazia A. (Archaeological Textiles Review, 2019)
The article presents the results of textile and fibre analysis of four textile fragments recovered during archaeological excavations at the site of Zawaydah, Naqada, in Upper Egypt. Although the main phase of the occupation at this site is ascribed to the Pre- and Protodynastic period (c. fourth millennium BC), the structural and fibre analyses of the textiles and the subsequent radiocarbon dating of two fragments provide evidence of later phases of site use, to be assigned to the Middle Kingdom, possibly the New Kingdom, and the Middle Ages (second millennium BC and second millennium AD). The article offers an insight into the Egyptian textiles of these latter time periods at the site, and highlights the importance of detailed structural and fibre analysis for acquiring dating information and informing the decisions to carry out further analyses, such as radiocarbon dating.